Personality traits and intrinsic motivation on academic performance - Saleh, Sofiazianti; Ashari, Zakiah Mohamad; Kosnin, Azlina Mohd (International Journal of Engineering and Technology, 2018)
There is a significant connection between personality traits and intrinsic motivation on academic performance. Personality has been highlighted by numerous researchers as one of human behaviour’s most important determinants. Intrinsic motivation is described as an individual who is willing and passionate towards a particular activity. Hence, through meta-analysis, this study aims to see if individual personal traits and being intrinsically motivated do influence students’ academic achievement. The study also aims in determining which personality traits instigate intrinsic motivation among students. After a meta-analysis of previous researches, there are several elements identified establishing the connection between personality and intrinsic motivation in students’ academic performance. They are: (1) behavioural inclinations mirrored in personality traits can have an impact on certain habits that influence academic achievement (2) cognitive ability is an indicator of an individual’s ability to do a task, personality traits indicate what the individual will do and motivation drives the individual and determines the amount of effort put into a particular task; (3) academic performance is predicted by personality traits particularly in motivation-related personality variables.